Leveraging the role of the microbiome in endometriosis: novel non-invasive and therapeutic approaches - Kalopedis, Eleni Andria; Zorgani, Amine; Zinovkin, Dmitry A.; Barri, Muruj; Wood, C. David; Pranjol, Md Zahidul I. (Frontiers in Immunology, 2025)
Endometriosis (EMS) is an oestrogen-dependent condition characterised by ectopic endometrial-like tissue growth with a chronic and inflammatory nature leading to severe symptoms and reduced quality of life. Emerging evidence implicates gut microbiome dysbiosis in EMS pathogenesis, driving chronic inflammation, immune dysfunction, and altered bacterial taxa within patient gut microbiome. This review examines the intricate relationship between gut dysbiosis and EMS, with a focus on immunomodulatory mechanisms and the downstream consequences of the bacterial contamination theory. It evaluates recent findings regarding microbial imbalances and microbial diversity, pinpointing gaps in current research that mandate further understanding. For example, while microbial markers like Lactobacillus depletion and elevated Escherichia coli have been observed in patients, their diagnostic potential remains poorly defined. Additionally, it addresses the broader implications of EMS, including its physical, mental and healthcare burdens. Simultaneously, critiquing current drawbacks in diagnostic and therapeutic strategies such as their invasiveness and limited efficacy. The review further evaluates novel microbiome-based strategies namely Lactobacillus-based probiotics and faecal microbiota transplantation (FMT), assessing their potential in modulating immune responses and alleviating EMS symptoms while considering associated challenges. Lastly, it highlights the emerging role of metabolomics in identifying non-invasive and diagnostic biomarkers like short-chain fatty acids (SCFAs), implicated in the interplay between microbial metabolites and immune signalling pathways in EMS.